Genes, Education, and Labor Market Outcomes: Evidence from the Health and Retirement Study - Nicholas W. Papageorge; Kevin Thom (Institute for the Study of Labor (IZA), 2016)
Recent advances have led to the discovery of specific genetic variants that predict educational attainment. We study how these variants, summarized as a genetic score variable, are associated with human capital accumulation and labor market outcomes in the Health and Retirement Study (HRS). We demonstrate that the same genetic score that predicts education is also associated with higher wages, but only among individuals with a college education. Moreover, the genetic gradient in wages has grown in more recent birth cohorts, consistent with interactions between technological change and labor market ability. We also show that individuals who grew up in economically disadvantaged households are less likely to go to college when compared to individuals with the same genetic score, but from higher-SES households. Our findings provide support for the idea that childhood SES is an important moderator of the economic returns to genetic endowments. Moreover, the finding that childhood poverty limits the educational attainment of high-ability individuals suggests the existence of unrealized human potential.
Keywords: I24; J24; 330; human capital; inequality; education; genes